2023
DOI: 10.1038/s41598-023-44845-6
|View full text |Cite
|
Sign up to set email alerts
|

SCAPS study on the effect of various hole transport layer on highly efficient 31.86% eco-friendly CZTS based solar cell

Rahutosh Ranjan,
Nikhil Anand,
Manish Nath Tripathi
et al.

Abstract: Copper Zinc Tin Sulphide (CZTS) is a propitious semiconductor for active absorber material in thin-film solar cells (SCs). Here, SC architecture comprising FTO/ZnS/CZTS/variable HTLs/Au is discussed. Fluorine-doped tin oxide (FTO) and gold (Au) are used as front and back contacts, respectively. Zinc sulphide (ZnS) is used as an active electron transport layer (ETL), while different Cu-based materials (Cu2O, CuO, CuI, and CuSCN) are used as hole transport layers (HTL). A one-dimensional solar cell capacitance s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The front contact is established with FTO, possessing a work function of 4•4 eV, while the back contact is made using Au, that has a work function of 5•1 eV. The cell's efficiency is significantly influenced by the work function of the metal employed for contact [21,32,33]. Metals like Pt and Au, which boast higher work functions compared to others, demonstrate superior efficiencies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The front contact is established with FTO, possessing a work function of 4•4 eV, while the back contact is made using Au, that has a work function of 5•1 eV. The cell's efficiency is significantly influenced by the work function of the metal employed for contact [21,32,33]. Metals like Pt and Au, which boast higher work functions compared to others, demonstrate superior efficiencies.…”
Section: Methodsmentioning
confidence: 99%
“…Many p-type materials serve as HTL, while n-type materials function as ETL in cell fabrication. Currently, copper-based materials, addressing issues such as low open circuit voltage (V oc ) and improved efficiency, are reported [21]. Materials with high mobility, conductivity, optical transmittance, low cost, and eco-friendly characteristics are advantageous for these layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCAPS (solar cell capacitance simulator) is a numerical simulation software for of heterojunction thin film solar cells. It has been developed at the University of Ghent in Belgium with LabWindows/CVI from National Instruments by Marc Burgelman et al [13]. The hybrid perovskites are characterized by a direct gap and a high absorption coefficient [14].…”
Section: Simulation Of Device and Modelingmentioning
confidence: 99%
“…PSCs performance has increased tremendously recently. It has shown that photovoltaic power conversion efficiency has jumped from 3.8% in 2009 [3] to 29.8% in 2023 [4][5]. Lead-based perovskite materials showed a high power conversion efficiency value but are not eco-friendly, which is harmful to humans and the environment [6].…”
Section: Introductionmentioning
confidence: 99%